2012
DOI: 10.1111/and.12039
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive system and antioxidants in oxidative stress induced by hypobaric hypoxia

Abstract: In Chile, due to the intensive activity developed in confining areas of the Andes Mountains ranging in altitude over 4000 asl, there has been an increasing intermittent movement of human resources to high altitude conditions. This unusual condition, defined as hypobaric hypoxia, affects notoriously in any living organism and there shows a series of physiological responses. Studies performed in rats under chronic hypobaric hypoxia and intermittent hypobaric hypoxia have registered changes in testicular morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
(75 reference statements)
0
18
0
1
Order By: Relevance
“…In amphibians, it has been suggested that local adaptation of egg coats to pH has a role in adaptive divergence (Shu et al 2015). Terrestrial examples include the yellow dung-fly (Scathophaga stercoraria) (temperature effects on eggs, Blanckenhorn et al 2014), and mammals (hypoxia and/or altitude effects on spermatogenesis and ovarian function, Vitzthum and Wiley 2003;Gonzalo Farias et al 2008;Parraguez et al 2014;Zepeda et al 2014)). Terrestrial examples include the yellow dung-fly (Scathophaga stercoraria) (temperature effects on eggs, Blanckenhorn et al 2014), and mammals (hypoxia and/or altitude effects on spermatogenesis and ovarian function, Vitzthum and Wiley 2003;Gonzalo Farias et al 2008;Parraguez et al 2014;Zepeda et al 2014)).…”
Section: Than Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…In amphibians, it has been suggested that local adaptation of egg coats to pH has a role in adaptive divergence (Shu et al 2015). Terrestrial examples include the yellow dung-fly (Scathophaga stercoraria) (temperature effects on eggs, Blanckenhorn et al 2014), and mammals (hypoxia and/or altitude effects on spermatogenesis and ovarian function, Vitzthum and Wiley 2003;Gonzalo Farias et al 2008;Parraguez et al 2014;Zepeda et al 2014)). Terrestrial examples include the yellow dung-fly (Scathophaga stercoraria) (temperature effects on eggs, Blanckenhorn et al 2014), and mammals (hypoxia and/or altitude effects on spermatogenesis and ovarian function, Vitzthum and Wiley 2003;Gonzalo Farias et al 2008;Parraguez et al 2014;Zepeda et al 2014)).…”
Section: Than Salinitymentioning
confidence: 99%
“…Other examples are temperature, which affects for example sperm performance in the mosquitofish Gambusia holbrooki (Adriaenssens et al 2012), and aquatic hypoxia, which for example reduces sperm motility and fertilization success in carp (Cyprinus carpio) (Wu 2009). Terrestrial examples include the yellow dung-fly (Scathophaga stercoraria) (temperature effects on eggs, Blanckenhorn et al 2014), and mammals (hypoxia and/or altitude effects on spermatogenesis and ovarian function, Vitzthum and Wiley 2003;Gonzalo Farias et al 2008;Parraguez et al 2014;Zepeda et al 2014)). In humans, this is only the case for immigrants, prompting Vitzhum and Wiley (2003) to suggest that the reproduction of humans is locally adapted to high altitudes.…”
Section: Than Salinitymentioning
confidence: 99%
“…Normal fertility in male results from a complex of physiological processes that determine the production, transport and ejaculation of an adequate number of spermatozoa with normal motility and fertilising capacity (Pescetto et al ., ). The pathophysiological role of hypoxia in male fertility is an intriguing issue that has been investigated in several experimental animal models (Zepeda et al ., , ) in which the exposure to altitude induces several reproductive changes including altered production of pituitary hormones and, in general, sexual hormones. Only few studies investigated the effects of acute hypoxia in human fertility (Okumura et al ., ) so that we have only few and contradictory data about the changes in male reproductive hormones or in seminal parameters in response to acute hypoxic exposure (Zepeda et al., , ) and, even less data, about the response to acute hypoxia combined with exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Study 14 showed that male sperm concentration tended to decrease in the high altitude hypoxia environment. Hypoxia can result in an increase of [15] in the level of germ cell apoptosis by oxidative stress, leading to lower levels of testosterone and related hormones, testicular tissue damage, which leads to reduced spermatogenesis and impaired testicular tissue.…”
Section: Common Physical Chemical Natural Environmentmentioning
confidence: 99%